Solubility of Cu, Ni, Mn in Boron-Rich Fe-B-C Alloys - Sukhova, O.V. (Physics and Chemistry of Solid State, 2021)
In the present study, the microstructure development and mechanical properties of the cast boron-rich Fe–B–C alloys cooled at 10 and 103 K/s were investigated as functions of alloying elements additions. These alloys were prepared in the following compositional ranges: B (10–14 wt.%), C (0.1–1.2 wt.%), M (5 wt.%), where M – Cu, Ni or Mn, balance Fe. Structural properties were characterized by quantitative metallography, X-Ray diffraction, scanning electron microscopy, and energy dispersive spectroscopy. Mechanical properties of the structural constituents, such as microhardness and fracture toughness, were measured by a Vickers indenter. Copper becomes negligibly incorporated into the phases Fe(B,C) and Fe2(B,C) of the Fe–B–C alloys, but solubility limit forces the remaining solute into the residual liquid. As a result, the globular Cu inclusions are seen in the structure. As compared with copper, nickel has higher solubility in the constituent phases, with preferential solubility observed in the Fe2(B,C) crystals, where Ni occupies Fe positions. Having limited solubility, nickel also forms secondary Ni4B3 phase at the Fe2(B,C) boundaries. Manganese was found to dissolve completely in the Fe–B–C alloys forming substitutional solid solutions preferentially with Fe(B,C) dendrites. By entering into the iron borides structure, Mn and Ni improve their ductility but lower microhardness. The peculiarities in the structure formation and properties of the doped boron-rich Fe–B–C alloys were explained with electronic structure of the alloying elements considered.